Co-pyrolysis of Rice Straw with High Density Polyethylene Bag - Muhammad Anshar (Science Faculty of Chiang Mai University, 2019)
A co-pyrolysis study was conducted to examine the characteristics of rice straw (RS) with high density polyethylene (HDPE) bag or plastic bag waste (PB) as the energy source. The determination of RS characteristics with PB mixtures of about 10%, 30%, and 50% was conducted by a thermogravimetric analysis at the temperatures of 30-800°C, time range of 0-82 min, heating rate of 10°C/min, and the flow rate of nitrogen of 50 ml/min. Kinetic studies were performed using the Arrhenius law to determine the activation energy. The dehydration process occurs at the temperature range of 40-110°C. Thermal decomposition occurs at the temperature range of 200-340°C, 400-500°C, and 580-670°C. The greater the percentage of PB in RS, the higher the value of Ea is produced. It is concluded that RS co-pyrolysis with PB had met the characteristic requirement as an energy source. The results can be implemented in gasification and combustion to overcome electricity shortage and MSW in Indonesia.